﻿﻿Congenital heart disease in children and adults Comparison of the Mid-term Results of Pulmonary Valve-sparing Strategy and Transannular Patch Repair in Tetralogy of Fallot - Arslan, Ozgur; Adademir, Taylan; Elibol, Ahmet; Ugur, Oguz; Aydın, Ebuzer; Kalender, Mehmet; Boyacıoğlu, Kamil; Aydemir, Numan Ali (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background : Between January 2006 and October 2009, 148 patients underwent total repair of tetralogy of Fallot (TOF). In 13 patients, palliative procedures were performed before total repair, while total correction was the initial and definitive procedure in 135 patients. Materials and methods: Patients who underwent total repair of TOF were evaluated retrospectively. They were assigned to one of two groups based on the right ventricular outflow tract (RVOT) reconstruction technique used: the transannular patch (TAP) group or the pulmonary valve-sparing strategy group. The two groups were compared with regard to age, weight, gender, annular structure, intraoperative right ventricular to left ventricular (RV/LV) pressure ratio, residual RVOT systolic gradient, RV diastolic parasternal long axis wall thickness, age-specific dilation, mortality, and morbidity during follow-up. Results : The percentage of patients with RV diastolic dilation (age specific) was significantly higher in the TAP group (88.9%) than in the pulmonary valve-sparing group (4.8%; p = 0.0009). The mid-term results of the pulmonary valve-sparing strategy were significantly superior to TAP repair in terms of preservation of right ventricular function. Conclusion : In order to preserve pulmonary valve function, TAP repair should be avoided when possible. The pulmonary valve-sparing strategy seems to result in less perioperative and long-term morbidity, and better preservation of RV function in the long-term, when compared to TAP repair.